The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.addr.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Oral drug delivery utilizing intestinal OATP transporters

Abstract: Abstract.Transporters play important roles in tissue distribution and urinary-and biliary-excretion of drugs and transporter molecules involved in those processes have been elucidated well. Furthermore, an involvement of efflux transporters such as P-glycoproteins, multidrug resistance associated protein 2, and breast cancer resistance protein as the intestinal absorption barrier and/or intestinal luminal secretion mechanisms has been demonstrated. However, although there are many suggestions for the contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 62 publications
(78 reference statements)
1
105
1
Order By: Relevance
“…We and others have already demonstrated that SN-38 is a substrate of OATP1B1 (Nozawa et al, 2005) and OATP1B3 (Yamaguchi et al, 2008), which are clinically important liver-specific uptake transporters. Although OATP2B1 is also expressed in the liver (Tamai et al, 2000), OATP2B1 is likely to be pharmacologically more important in the intestine since OATP2B1, but not OATP1B1 or OATP1B3, is expressed in small-intestinal tissues (Tamai, 2012;Shirasaka et al, 2014). In our previous study, we failed to find a significant increase of SN-38 uptake by OATP2B1-expressing Xenopus oocytes (Nozawa et al, 2005).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We and others have already demonstrated that SN-38 is a substrate of OATP1B1 (Nozawa et al, 2005) and OATP1B3 (Yamaguchi et al, 2008), which are clinically important liver-specific uptake transporters. Although OATP2B1 is also expressed in the liver (Tamai et al, 2000), OATP2B1 is likely to be pharmacologically more important in the intestine since OATP2B1, but not OATP1B1 or OATP1B3, is expressed in small-intestinal tissues (Tamai, 2012;Shirasaka et al, 2014). In our previous study, we failed to find a significant increase of SN-38 uptake by OATP2B1-expressing Xenopus oocytes (Nozawa et al, 2005).…”
Section: Discussionmentioning
confidence: 73%
“…These results suggest that inhibition of OATP2B1 in enterocytes would contribute to effective treatment of SN-38-induced late-onset diarrhea. We next evaluated the effect of fruit juices on OATP2B1-mediated transport of SN-38 since fruit juices interact with OATP2B1 and affect intestinal absorption of substrate drugs (Imanaga et al, 2011;Tamai, 2012;Tamai and Nakanishi, 2013). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that bioavailability of fexofenadine is decreased in individuals with the OATP2B1 c.1457C.T allele and is also decreased in the presence of AJ (Imanaga et al, 2011). These observations imply that AJ interacts with fexofenadine through inhibition of OATP2B1-mediated absorption, although a contribution of OATP1A2 to intestinal AJ-drug interactions cannot be ruled out (Kobayashi et al, 2003;Shirasaka et al, 2010a;Tamai, 2012). Involvement of OATP2B1 in FJdrug interaction was also demonstrated by our recent report describing that coincubation with GFJ, OJ, and AJ significantly inhibited OATP2B1-mediated uptake of estrone-3-sulfate with apparent IC 50 values in the order of GFJ , OJ , AJ (Shirasaka et al, 2013).…”
Section: Introductionmentioning
confidence: 74%
“…31) In addition, organic anion transporting polypeptide (OATP) family, such as OATP1A2 (also named SLCO1A2) and OATP2B1 (also named SLCO2B1), may also contribute to the cellular uptake of exendin-4, which has been reported to mediate intestinal absorption of several drugs. 32) The first step of this study was to demonstrate whether active transport and endocytosis transport is involved in the exendin-4 transport across MDCK cell monolayars. Experimental results of time and concentration effect showed that the cumulative permeation amount of exendin-4 was increased linearly with the concentration or time increasing, and no saturation phenomenon was observed over all time period and concentration range, which were the typical characteristics of passive diffusion.…”
Section: Discussionmentioning
confidence: 99%